Digital Innovation during COVID-19: Transforming Challenges to Opportunities - Yu Chen; Roldan, Malu (Communications of the Association for Information Systems, 2021)
The coronavirus disease of 2019 (COVID-19) swiftly changed almost all aspects of our lives and society. In this paper, we depict course adjustments that we made to an undergraduate digital innovation course project, called Innovation Farm (IF), in response to the pandemic. Designed as an in-person course project, IF requires students to create AIpowered Android apps to address important social issues. As stay-at-home orders came into effect in March, 2020, we shifted the course to the online modality refocused its student topics to address social issues that COVID-19 has engendered. Accordingly, we also discuss three challenges that we faced and the strategies we employed to cope with them; namely, framing students' social innovation topics in the COVID-19 context, using virtual studios for online groupwork, and hosting a virtual pitch competition. Surprisingly, these strategies not only addressed the challenges but also created unintended benefits and opportunities. We hope to encourage educators to consider the possibilities in transforming challenges to opportunities during these unprecedented times.
Keywords: Réservé UdeM; Rôle des universités; États-Unis